2021
DOI: 10.1111/jocs.15964
|View full text |Cite
|
Sign up to set email alerts
|

Common arterial trunk in the era of high prenatal detection rates: Results of neonatal palliation and primary repair

Abstract: Objective We reviewed our center's experience with common arterial trunk. Methods We included those with common arterial trunk in Nevada with estimated delivery dates or birth dates between June 2006 and May 2021. We excluded patients with functionally univentricular hearts. Results We identified a total of 39: 32 prenatally and 7 postnatally. Of the 32 prenatally detected, 2 had elective termination, 2 had fetal demise, and 28 were live‐born. Of the 7 postnatally diagnosed, 6 had prenatal care without a fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The current standard of care is neonatal repair of the defect, with reconstruction of the right ventricular outflow tract by various techniques [3][4][5] . Although there has been a decrease in surgical mortality and morbidity over time [6][7][8] , interrupted aortic arch, truncal valve dysfunction with insufficiency or stenosis, coronary abnormalities and DiGeorge syndrome remain risk factors for adverse outcome 3,7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The current standard of care is neonatal repair of the defect, with reconstruction of the right ventricular outflow tract by various techniques [3][4][5] . Although there has been a decrease in surgical mortality and morbidity over time [6][7][8] , interrupted aortic arch, truncal valve dysfunction with insufficiency or stenosis, coronary abnormalities and DiGeorge syndrome remain risk factors for adverse outcome 3,7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the challenging nature of accurate CAT assessment before delivery, many cases may be misdiagnosed during prenatal ultrasonography screening. 5 The prevalence of complex intra-and extra-cardiac malformations was 51.8% and 27.8%, respectively, in a large proportion of fetuses in this study, and only 20.4% of the fetuses were isolated CAT. In comparison, the incidence of CAT complicated with intra-cardiac malformations was higher (54.55%), and the incidence of extra-cardiac malformations was consistent with that reported by Gomez et al 6 However, Abel et al reported a high incidence of extra-cardiac malformations of 58.8%.…”
Section: Discussionmentioning
confidence: 48%
“…Due to the challenging nature of accurate CAT assessment before delivery, many cases may be misdiagnosed during prenatal ultrasonography screening 5 . The prevalence of complex intra‐ and extra‐cardiac malformations was 51.8% and 27.8%, respectively, in a large proportion of fetuses in this study, and only 20.4% of the fetuses were isolated CAT.…”
Section: Discussionmentioning
confidence: 67%
“…As an accurate prenatal assessment of CAT is extremely challenging, many cases may be misdiagnosed during prenatal ultrasonography screening. 5 A large proportion of foetuses in this study had complex intra-cardiac and extra-cardiac malformations, with prevalence rates of 51.8% and 27.8%, respectively, and only 20.4% of the foetuses were isolated. In contrast, the incidence of CAT complicated with intra-cardiac malformations was higher (51.8%), and the incidence of extra-cardiac malformations was consistent with that reported by Gomez et al 6 However, Abel et al reported that the incidence of extra-cardiac malformations was 58.8%.…”
Section: Discussionmentioning
confidence: 66%